EFFECTS OF PHYSICAL THERAPY IN MUSCULAR STRENGTH AND BALANCE, PAIN RELIEF AND FUNCTIONAL CAPACITY IN PATIENTS WITH PATELLOFEMORAL PAIN SYNDROME - Dobreanu (căs. Ioja) Ioana-Bianca; Cojocariu Adrian (Sport şi Societate)
Based on the research carried out from specialized sources, we can conclude that femoral-patellar pain syndrome is a clinical entity that leads to the appearance of anteriorknee pain, in patients without pathological changes present in the cartilage of the femoral-patellar joint.Studies in the specialized literature demonstrate that a physical therapist can adapt an individual treatment plan for each patient depending on the underlying pathology.Considering the importance of the knee joint in everyday life, both for carrying out daily activities and for carrying out professional activities, we can conclude that its recovery is extremely important.The production mechanisms of the femoro-patellar syndrome are multiple, and this requires the implementation of a recovery program as effective as possible, based on the most accurate and detailed assessment.Current imaging techniques can provide us with important data regarding the situation of the knee joint, which makes the diagnosis of patellofemoral syndrome easier. Orthopedic treatment can be considered adjuvant in combating the pain caused by femoral-patellar syndrome if it is associated with an individualized and well-structured physical therapy program.Surgical interventions are only indicated for patients in whom an anatomical defect of the bone structures or the pathological alignment of the patella maintains the destruction of the cartilage. After any type of surgical intervention, it is mandatory to establish specialized physiotherapy programs with specific objectives, in order to ensure a high post-operative success rate.